Modelling of the AC Breakdown Voltage of Point- Plane Air Gaps with Insulating Barrier - Abdelghani Rouini; Djillali Mahi (Institute of Advanced Engineering and Science, 2015)
High voltage device dimensioning requires the prediction of the withstand voltage for test conditions like impulses, surges and AC voltage. There is a large need of designer to have reliable design criteria and well-defined simulation procedure for device development. This parametric study is based on the methodology of experimental designs. This method allowed us to propose a mathematical polynomial model. The objective of this paper is to study the discharge phenomena for a point –plane air interval with insulating barrier between them. Firstly on experimental study of a laboratory setup that we designed to carry out the influence of parameters (geometrical) involved in the process of breakdown. The distance between electrodes and different parameters of the barrier such as its position between electrodes dimension and its holes is studied . The barrier acts as a geometrical obstacle against the direct propagation of discharge. Secondly, using results obtained by the experimental setup , we have experiments design methodology of technique to predict the breakdown threshold voltage.